2006
DOI: 10.5565/rev/papers/v79n0.800
|View full text |Cite
|
Sign up to set email alerts
|

Sociología de la juventud y análisis comparativo en los estados miembros de la Unión Europea

Abstract: The central aim of the present article is to reflect on the possible contribution sociological comparative youth research in Europe can offer for a better understanding of youth life in the EU member states. With this purpose it analyses in a first step, the structural conditions under which young Europeans grow up today, in the context of globalisation and Europeanization, asking about the consequences such processes have on young people's insertion in society. The analysis of youth and youth developed here i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Indeed, the nding that poorer subjective health status was associated with an increased risk of suicidal ideation highlights the importance of health as a crucial factor for young individuals. Numerous studies have demonstrated a correlation between subjective health and suicidal ideation [35,51,52]. Young adulthood is when growth and development end and aging begins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the nding that poorer subjective health status was associated with an increased risk of suicidal ideation highlights the importance of health as a crucial factor for young individuals. Numerous studies have demonstrated a correlation between subjective health and suicidal ideation [35,51,52]. Young adulthood is when growth and development end and aging begins.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, health characteristics, such as self-rated health and stress levels [21,28,29], and health behaviors, including sleep duration, alcohol consumption, and smoking, have been found to in uence suicidal ideation [30][31][32]. Previous research has identi ed being female, low education level, low income, poor health status, high perceived stress, smoking, and being unmarried as factors related to depression [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The question of inequality emerges in studies of youth transition since different pathways are available to young people from different social backgrounds and since they depend on their parents' social position (Heinz, 2009a). As a consequence of structural changes in the economy and economic recession, less qualified groups from a lower social background are more often faced with unemployment, labour market exclusion and social marginalisation without changes in social mobility (Bendit, 2006). In that manner, studies of youth transition are reaching conclusions similar to those of the social reproduction theory, which argues that chances of achieving career goals are higher for young people from privileged positions (Bourdieu and Passeron, 1990;Anyon, 1980Anyon, , 2006Bowles and Gintis, 1976).…”
Section: Sociological Perspectivementioning
confidence: 99%